AB0404 Apelin concentrations are associated with a reduced left atrial volume index and improved systolic function in patients with rheumatoid arthritis. (12th June 2018) - Gunter, S.; Robinson, C.; Tsang, L.; Dessein, P.H.; Millen, A.M.
Abstract : Background: We recently reported that apelin concentrations are associated with reduced atherosclerosis and plaque vulnerability as well as improved aortic function in rheumatoid arthritis (RA) 1, 2 . These relations were influenced by RA characteristics 1, 2 . Besides protecting against atherosclerosis, apelin is also a vasoactive peptide that improves cardiac contractility. In this regard, patients with RA experience a 2-fold increased risk of developing heart failure 3 . RA patients often demonstrate diastolic dysfunction and heart failure with a preserved ejection fraction (HFpEF). Traditional cardiovascular risk factors do not fully explain the increased heart failure incidence in this population. Metabolic risk factor driven inflammation is highly implicated in HFpEF. Objectives: This study aimed to determine whether apelin can impact left ventricular function in RA and whether disease characteristics can modify this potential effect. Methods: Relationships of apelin concentrations with echocardiographically determined markers of systolic and diastolic function including stroke volume, endocardial fractional shortening, midwall fractional shortening, ejection fraction, relative wall thickness, left ventricular mass, mitral inflow (E/A), filling pressure (E/e') and left atrial volume index (LAVI) were determined in multivariable regression models among 169 patients without established cardiovascular disease. Results: In demographic characteristic adjusted analysis, rheumatoid factor (RF) positivity, joint deformity counts, and CRP were associated with increased apelin concentrations (p=0.01, 0.02 and 0.05, respectively). Apelin was associated with a reduced LAVI [β(SE)=-4.6 (2.2); p=0.04] but not with E/A, lateral e' or E/e' (p>0.05 for all). RA characteristics including disease duration, CRP, erythrocyte sedimentation rate (ESR), RF positivity, and joint deformity counts did not impact apelin concentration-diastolic function marker relationships (interaction p values>0.05). Apelin levels were associated with increased endocardial fractional shortening [β(SE)=5.99 (2.97); p=0.04] and midwall fractional shortening [β(SE)=6.92 (3.0); p=0.03]. The ESR and anti-citrullinated peptide antibody (ACPA) status impacted the apelin level-endocardial fractional shortening relationships (interaction p=0.05 and 0.01, respectively). In stratified analysis, apelin concentrations were associated with improved endocardial fractional shortening in those with [β(SE)=14.1 (3.9); p=0.001] but not without an ESR >12 mm/hr (median value), and in those with [β(SE)=8.2 (3.7); p=0.03] but not without ACPA positivity. Conclusions: In RA, apelin concentrations are associated with a reduced LAVI irrespective of RA activity and severity characteristics. Apelin concentrations are also associated with improved endocardial fractional shortening in patients with RA, particularly in those with high-grade inflammation and ACPA positivity. Whether apelin can improve left ventricular systolic and diastolic function in RA merits further exploration in longitudinal studies. References: [1] Gunter S, et al. Atherosclerosis2017;256–75.81. [2] Gunter S, et al. Clinical Rheumatology2018:in press. [3] Nicola PJ, et al. Arthritis Rheum2005:52;412–20. Disclosure of Interest: None declared